Teaching Macbeth to muslim learners: an Islamic perspective - Othman, Khairiah; Mohamed Salleh, Rabiah Tul Adawiyah; Aziz, Fadhillah (2011)
The concept of tragedy is a prevalent theme in Shakespearean works. Al-Attas (1993), one of the renowned Muslim scholars, however, emphasizes that this concept is foreign to Muslims and needs to be eliminated from western texts. Employing al-Attas’s methodology of Islamization of knowledge, Macbeth, the shortest but the most intense Shakespearean tragedy, will be evaluated and Islamized. This paper offers some suggestions on how to utilize this text to Muslim learners.